2013
DOI: 10.2224/sbp.2013.41.5.819
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Extroversion and Introversion on Language-Learning Behaviors

Abstract: Despite the fact that personality factors and learning strategies are of great importance in success with language learning, the link between extroversion and introversion and languagelearning strategies has received little attention from researchers. Therefore, I investigated whether or not there is any correlation between these personality traits and language-learning strategies. Participants in the study were 106 extroverted and 94 introverted students. The Eysenck Personality Questionnaire (EPQ) and the St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 11 publications
3
27
1
1
Order By: Relevance
“…Based on the data analysis, it can be concluded that the self-confidence of students has a significant impact on their achievement [27]. In developing the personality types of having self-confidence, the findings show that introverted learners are actively using goal-oriented specific behaviors while extroverted learners are using more interpersonal communication techniques [28]. Overall, it was found that cognitive anxiety reduced and self-confidence increase by motivational talk [29].…”
Section: Related Review Of Literaturementioning
confidence: 93%
“…Based on the data analysis, it can be concluded that the self-confidence of students has a significant impact on their achievement [27]. In developing the personality types of having self-confidence, the findings show that introverted learners are actively using goal-oriented specific behaviors while extroverted learners are using more interpersonal communication techniques [28]. Overall, it was found that cognitive anxiety reduced and self-confidence increase by motivational talk [29].…”
Section: Related Review Of Literaturementioning
confidence: 93%
“…Furthermore, most research dealing with this topic points out features such as Openness to experience and Conscientiousness and fewer authors investigate the effects of all five personality types on the degree of use of these strategies. In addition, in the research, Myers-Briggs Type Indicators (Myers, Mc-Caulley, Quenk, & Hammer, 1998) are more commonly used, with an emphasis on examining differences in the application of these strategies between personality types (Chen & Hung, 2012;Kayaoglu, 2013). Finally, with the exception of Fazeli (2011aFazeli ( , 2011bFazeli ( , 2012aFazeli ( , 2012bFazeli ( , 2012cFazeli ( , 2012d) regression analysis has not been used in this kind of research so far.…”
Section: Personality Type and Language Learning Strategiesmentioning
confidence: 99%
“…Introverted learners are usually less successful than extroverted learners when it comes to learning languages [14]. The main reason for this is that introversion is related to unsociable, quiet, and passive behavior, which is not generally conducive to language acquisition.…”
Section: The Relationship Between the Three Traits And Social Identitymentioning
confidence: 99%